One year outcome of patients with infective endocarditic Cairo universty experience - Batool Mostafa Almogheer; Hussein Hasan Rizk; Wafaa Anwar Elaroussy; Waleed Abdalsalam Ammar (Cairo : Batool Mostafa Almogheer, 2010)
Aim : Determine incdence causes and predictors of in hospital and late post discharge mortality in patients with IE . Conclusion : IE mortality is high in Egypt . Female gender is the most powerful predictor of mortality followed by HF. Mortality in early months following discharge was related to the complications of IE ; emphasizing the importance of post discharge follow-up
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Cardiology
Issued also as CD
Keywords: Endocarditic; Heart failure; out come